VIEWS OF PROFESSOR M. I. KHLEBNIKOV (1840-1880) ON THEORY OF STATE AND LAW - Holovko, Oleksandr; Hrechenko, Volodymyr (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2021)
Introduction. The task of development the science History of the doctrines of Law and State means to turn in particular to domestic experience. The article analyzes the creative work of the historian and theorist of law of the XIX century M. I. Khlebnikov. His name has been undeservedly forgotten by modern scientists. As a result the study of his scientific achievements makes a more complete picture of the development of domestic doctrines of State and Law. Summary of the main research results. In the M. I. Khlebnikov’s manuscript “Law and State in their mutual relations: a study of the origin, essence, basic principles and methods of civilization in general” (published in 1874, 600 pages), considered a significant number of scientific problems of origin and essence of State and Law, their connection with the development of human civilization in general and in individual countries in particular. The main attention is paid to the analysis of the main provisions of many legal scientists of the XVII – XIX centuries, who studied these problems on different methodological bases. The author critically evaluated most of these views and commented on them. After these comments we can make a generalization about his views on these problems. He extensively quoted the works of different scientists of different periods and, most often, critically evaluates their opinions. The book evaluates the doctrines and theories of such scientists as Plato, Aristotle, J. Locke, T. Hobbs, I. Kant, G. V. F. Hegel, O. Comte and many others. Conclusions. M. I. Khlebnikov was one of the most capable and knowledgeable representatives of pre-revolutionary legal science. Despite some contradictions of his views, in the book of the scientist we can see the beginning of his own original integrative (synthetic) doctrine of the State and Law. As for us, only his premature death did not allow the scientist to form this theory.